The development of self-definition and relatedness in emerging adulthood and their role in the development of depressive symptoms. (July 2016) - Kopala-Sibley, Daniel C; Zuroff, David C; Hermanto, Nicola; Joyal-Desmarais, Keven
According to Blatt (2004; Blatt & Luyten, 2009) and others (e.g., Beck, Epstein, Harrison, & Emery, 1983), establishing positive self-definition and mature relatedness to others represent core lifespan developmental tasks. In a sample of emerging adults, this study examined the effects of the quality of one close friendship and changes in romantic relationship status on the development of maladaptive personality traits from each domain (self-criticism and neediness and connectedness), and the effects of changes in these personality factors on the development of depressive symptoms. Participants consisted of 82 (13 male) emerging adults ( M age = 19.00, SD = 0.75) and a single corresponding close friend. At baseline, participants and their friends completed measures of the quality of their relationship (i.e., acceptance and autonomy support). At baseline and again 12 months later, participants completed measures of self-criticism, neediness, connectedness, depressive symptoms, and current romantic relationship status. Adjusting for gender and baseline age, structural equation models showed that better friendship quality predicted decreases in self-criticism, which in turn predicted lower levels of depressive symptoms. Entering into a romantic relationship predicted increases in connectedness. Connectedness was unrelated to depression, although increases in neediness over time predicted increases in depressive symptoms. Results highlight the role of one close friend and changes in romantic relationship status in the development of self-definition and relatedness during emerging adulthood, and the role of those personality factors in the development of depression.